Peran Deformasi Pensesaran Mendatar Terhadap Pembentukan Beberapa Cekungan Kecil Paleogen di Sumatera Barat dan Jambi - Bachri, Syaiful (Jurnal Geologi dan Sumberdaya Mineral, 2006)
Peleogene small basins (sub-basins) occur in West Sumatra and Jambi, either in the volcanic arc or in the southwestern margin of the Central Sumatera Basin area. According to previous reports, the small basins were developed due to regional extensional tectonics. On the basis of radar image interpretation, supported by field observation on some structural features, the small basins are interpreted to have been formed by a regional strike-slip system related to deformation of the Sumatera Fault. Smaller scaled structures may be developed within the strike-slip fault zone, either as strike-slip faults, normal faults, or combined strike-slip and normal faults, forming a braided structural pattern. Convergent movement within the braided zone may result in uplifting of some blocks, whilst the divergent movement will result in a low morphology to form relatively small basins. Keywords: Paleogene Basin, strike-slip deformation, Sumatera Fault, convergent, divergent